Advertising creative : strategy, copy + design - Altstiel, Tom; Altstiel, Tom; Grow, Jean (Sage Publications, 2010)
Written in an accessible style, Advertising Creative gets right to the point of advertising by stressing key principles, illustrating them, and then providing practical information students and working professionals can use.